Association of serum Maresin-1 levels with insulin-resistance indices in obese individuals - Deniz, Levent; Yardim, Meltem; Saltabas, Mehmet Akif; Akkoc, Ramazan Fazil (Kare Publ, 2025)
INTRODUCTION: This study aimed to investigate serum Maresin-1 (MaR1) levels among obese, overweight, and normal-weight groups, as well as to evaluate their association with various metabolic parameters, including insulin resistance-related indices and lipid profiles. METHODS: Ninety subjects were classified into three distinct groups in terms of body mass index (BMI). Using a median MaR1 value of 608 pg/mL as the threshold, the participants were also categorized into two distinct groups. Serum MaR1 levels were quantified via an ELISA. The study also evaluated several other indicators: metabolic score for insulin resistance (METS-IR), triglyceride glucose-body mass index (TyG-BMI), HbA1c, and various components of the lipid profile. RESULTS: MaR1 levels were significantly lower in the obese and overweight categories compared to the normal-weight categories. Nevertheless, no statistically significant difference was observed in the MaR1 levels between the obese and overweight groups. MaR1 levels were negatively linked to METS-IR (r=-0.444, p<0.001) and TyG-BMI (r=-0.427, p<0.001), whereas quantitative insulin sensitivity check index (r=0.318, p=0.002) levels were positively correlated. METS-IR had the highest AUC value (0.706), with 73.3% sensitivity and 57.8% specificity to identify high levels of MaR1 (p<0.001). DISCUSSION AND CONCLUSION: Ordinal logistic regression revealed a significant independent relationship between MaR1 levels and BMI categories. The close association between MaR1 and metabolic indices such as METS-IR and TyG-BMI suggests its role in insulin sensitivity and obesity-associated metabolic disorders.
Keywords: Insulin resistance; Maresin-1; METS-IR; obesity; specialized pro-resolving mediators; TyG-BMI